Ekstrak Etanol Daun Binahong (Anredera cordifolia) di Berbagai Tingkat Konsentrasi terhadap Bakteri Staphylococcus aureus dan Pseudomonas aeruginosa - Wiwi Azlina Syawalien; Andreas Putro Ragil Santoso (Pusat Riset dan Inovasi Nasional, 2025)
Burns can cause infection, hinder healing, and increase the risk of long-term complications. Staphylococcus aureus and Pseudomonas aeruginosa often infect burn wounds in general, infections are treated with antibiotics, but continued use of antibiotics can cause bacterial resistance. Binahong leaves (Anredera cordifolia) have potential as a substitute for antibiotics because of their antibacterial properties from active compounds such as alkaloids, polyphenols, tannins, saponins and ascorbic acid. This research aims to activate the antibacterial ability of binahong leaf ethanol extract against S. aureus and P. aeruginosa. This research uses an experimental method with a control group design using diffusion and dilution methods at varying concentrations. Statistical analysis of the inhibition zone showed that there was a significance difference of <0.05 between treatment groups. In the solid diluted method, S. aureus obtained an MIC value of 10.5% and a MBC of 11.5%, whereas P. aeruginosa had an MIC of 14.5% and a MBC of 15%. The results showed that the ethanol extract of binahong leaves was more sensitive to S. aureus than P. aeruginosa.